Hands-On Algorithms for Computer Vision : Learn how to use the best and most practical computer vision algorithms using OpenCV /: Learn how to use the best and most practical computer vision algorithms using OpenCV. (2018) - Ahmadi Tazehkandi, Amin
No abstract available